Peningkatan Pengetahuan Tentang PMT Pada Kader Posyandu Kalurahan Sendangsari Sebagai Upaya Penanggulangan Stunting Melalui Self Help Group - Sutantri; Zikri Alhalawi; Chaidar Muhammad; Angelia Friska Tendean (Jurnal Pengabdian Pada Masyarakat, 2022)
INCREASİNG KNOWLEDGE ABOUT PMT FOR POSYANDU CADRE İN SENDANGSARİ VİLLAGE AS AN EFFORT TO PREVENT STUNTİNG THROUGH SELF HELP GROUP (SHG). The sustainable development goal in 2030 is to eliminate nutritional problems, one of which is by accelerating stunting. Posyandu cadres play an important role in the success of stunting in the community. The purpose of this community service activity is to increase the knowledge of toddler Posyandu cadres about providing additional food as an effort to prevent stunting in the Sendangsari Village. The method of activities carried out to increase the knowledge of posyandu cadres is a self help group with the topic of stunting and complementary feeding for toddlers. Data analysis uses frequency distribution and percentages to describe the level of knowledge of posyandu cadres. The results of community service activities carried out by the community service team showed the level of knowledge about stunting before an average of 97% increased to 100%. Meanwhile, the level of knowledge about supplementary feeding before 75% (n=31) was in a good category, increasing to 100% (n=41) in the good category. Conclusion Self help groups can increase the knowledge of posyandu cadres. Good knowledge will affect a person's behavior. Knowledge of posyandu cadres must always be increased to prevent or overcome stunting. Posyandu cadres become extensions of health workers to be able to reach the community in community health development.